DEVELOPING E-LEARNING MEDIA FOR ESP LEARNING OF ENGLISH FOR NURSING STUDENTS - Abdul Halim; Asslia Johar Latipah; Azhar Aziz Lubis (STAI Hubbulwathan Duri, 2019)
The purpose of this research was to develop e-learning media for ESP learning of English for Nursing Students. The development of English for specific needs has rapidly increased as the demand for tailor-made language learning raised. Following the current trend of industrial revolution 4.0, the need of ESP e-learning media is critically necessary. The study used Research Development (RD) model. There are some stages in RD model namely (1) Research and Information Collecting, (2) Planning, (3) Developing Preliminary Form of Product, (4) Preliminary Field Testing, (5) Main Product Revision, (6) Main Field Testing, (7) Operational Product Revision, (8) Operational Field Testing, (9) Final Product Revision and (10) Dissemination and Implementation. However, due to the limitation of the study, only five stages were conducted. The results indicated that the product of e-learning media for ESP learning of English for Nursing students was ready to use